The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.1186/s12870-022-03822-3
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptomic and alternative splicing analyses provide insights into the roles of exogenous salicylic acid ameliorating waxy maize seedling growth under heat stress

Abstract: Background Salicylic acid (SA) is a phytohormone which works to regulate the abiotic stress response of plants. However, the molecular mechanism by which SA mediates heat tolerance in waxy maize (Zea mays L. sinsensis Kulesh) remains unknown. Results Two varieties of waxy maize seedlings, heat-tolerant ‘Yunuo7’ (Y7) and heat-sensitive ‘Suyunuo5’ (S5), were pretreated with SA prior to heat stress (HTS). After treatment, physiological and transcripto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 81 publications
0
3
0
Order By: Relevance
“…Several morphological, physiological, biochemical, molecular and yield-related traits and processes in maize are negatively impacted under heat stress conditions. Under high-temperature stress, the chlorophyll content and photosynthetic rate of maize are decreased, and the cell membrane and antioxidant system are damaged [4,17,29]. These physiological changes can affect the growth and development of maize, ultimately leading to a decline in yield [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…Several morphological, physiological, biochemical, molecular and yield-related traits and processes in maize are negatively impacted under heat stress conditions. Under high-temperature stress, the chlorophyll content and photosynthetic rate of maize are decreased, and the cell membrane and antioxidant system are damaged [4,17,29]. These physiological changes can affect the growth and development of maize, ultimately leading to a decline in yield [30][31][32].…”
Section: Discussionmentioning
confidence: 99%
“…The activities of lignin biosynthesis pathway enzymes, such as PAL, 4CL, CCR and HCT, and the lignin content were all analyzed using ELISA kits (Shanghai Enzyme-linked Biotechnology Co., Ltd, Shanghai, China) according to the manufacturer's instructions (Guo et al, 2022). Each treatment repeated three times.…”
Section: Determination Of Enzyme Activity and Lignin Contentmentioning
confidence: 99%
“…One of the most prominent roles of SA is in stress tolerance of plants, where it acts as a signaling molecule that induces resistance (Sharma et al 2020). Rady and Mohamed (2015), Zulfiqar et al (2020), andGuo et al (2022) reported that 1 mM, 50 mgÁL À1 and 0.75 mM SA effectively improved growth and yield of common bean (Phaseolus vulgaris L.), gladiolus (Gladiolus grandifloras L.), and maize (Zea mays L.) plants under normal or environmental stress conditions such as salt and heat stress, respectively. Although SA is effective, its excessive application could be associated with water and air pollution (Kaya et al 2023).…”
mentioning
confidence: 99%